Pembuatan Nanopartikel Zinc Oxide melalui Metode Sintesis Hijau menggunakan Ekstrak Daun Kersen (Muntingia calabura L.) - Adinda Mahesa Putri; Sri Handani; Afdhal Muttaqin (Jurnal Fisika Unand, 2026)
This study aims to synthesize ZnO nanoparticles through a green synthesis approach utilizing Muntingia calabura L. leaf extract as a natural bioreducing and stabilizing agent. The green synthesis route was chosen for its environmental friendliness and sustainability compared to conventional chemical methods that rely on toxic reagents and high energy consumption. The Muntingia calabura leaf extract, rich in secondary metabolites such as flavonoids, polyphenols, and tannins, acted as reducing agents to convert Zn²⁺ ions into ZnO nanoparticles. The synthesis involved mixing various extract concentrations (5%, 10%, 15%) with 0.05 M zinc acetate dihydrate, followed by calcination at 600°C. UV-Vis spectra showed an absorption peak around 370 nm, confirming the formation of ZnO nanoparticles. XRD analysis indicated a hexagonal wurtzite crystal structure with an average crystallite size of 20–40 nm, while SEM revealed nearly spherical morphology with uniform distribution. FTIR confirmed the presence of –OH and C=O functional groups from phenolic compounds that acted as capping agents. These findings highlight the promising role of Muntingia calabura leaf extract as a sustainable biogenic source for ZnO nanoparticle synthesis.